Varied role of organic carboxylate dizwitterions and anionic donors in mixed-ligand uranyl ion coordination polymers. Issue 44 (27th October 2022) - Kusumoto, Sotaro; Atoini, Youssef; Masuda, Shunya; Koide, Yoshihiro; Kim, Jee Young; Hayami, Shinya; Kim, Yang; Harrowfield, Jack; Thuéry, Pierre
Abstract : Two organic dizwitterions were combined with various anionic donors to generate a series of five uranyl ion complexes crystallizing as mono- or diperiodic coordination polymers, with separation into two distinct networks in one case. Abstract : The dizwitterionic dicarboxylate ligands 1, 1′-[(2, 3, 5, 6-tetramethylbenzene-1, 4-diyl)bis(methylene)]bis(pyridin-1-ium-4-carboxylate) ( p L) and 1, 1′-[(2, 3, 5, 6-tetramethylbenzene-1, 4-diyl)bis(methylene)]bis(pyridin-1-ium-3-carboxylate) ( m L) have been reacted with uranyl cations under solvo-hydrothermal conditions to generate a series of five complexes containing also additional anionic donors. [UO2 ( p L)(H2 PM)(H2 O)2 ]·DMA·H2 O (1 ), where H4 PM is pyromellitic acid and DMA is dimethylacetamide, and [(UO2 )2 ( p L)3 (3-SB)2 ]·8H2 O (2 ), where 3-SB 2− is 3-sulfobenzoate, crystallize as monoperiodic coordination polymers, linear or including dinuclear rings, respectively, in which the p L ligands are bridging and the anionic species are merely decorating and involved in hydrogen bonding. p L connects four metal cations in [(UO2 )2 ( p L)(2-SB)2 ]·1.5H2 O (3 ) and, associated with the chelating and bridging 2-sulfobenzoate (2-SB 2− ) ligand, it gives a diperiodic network with the kgm topology. [(UO2 )3 ( m L)(O)2 (OH)(H2 O)](NO3 )0.8 Cl0.2 ·3H2 O (4 ) contains oxo- and hydroxo-bridged ribbon-like chains connected by m L linkers to form a cationic diperiodic network. In contrast, two independent, polyanionic and polycationic networks in a 2 : 1 ratio are formed in [(UO2 )2 ( m L)3 (H2 O)2 ][(UO2 )2 (TDC)3 ]2 ·10H2 O (5 ), involving either m L or TDC 2− (2, 5-thiophenedicarboxylate) ligands; both networks have the hcb topological type, albeit with very different cell shapes.